PHYTOCHEMISTRY AND PHARMACOLOGICAL ACTIVITY OF PSIDIUM GUAJAVA (LINNAEUS 1753) AN OVERVIEW (Journal of Pharmaceutical Negative Results, 2023)
This review aims to provide the information regarding the phytochemistry and pharmacological activity of Psidium guajava (guava) belonging to Myrtaceae family of phylum Magnoliophyta and class Magnoliopsida. This multibeneficial tree found in almost all regions, but dry climatic regions are most preferable for the cultivation. Flavonoids, polyphenolic compounds, pentacyclic triterpenoids, carotenoids, essential oils, ester and aldehyde are the important active constituents found in guava. The leaves, fruits, bark, stem, roots of this plant are the most commonly used parts and these parts carry different pharmacological activities ranging from antimicrobial to anti-cancer properties. Guava fruit contains carbohydrates, proteins, fats and high-water content. Bark contains tannin, resins, while roots contain sterol, gallic acid, carbohydrate and salt. According to a research, guava leaf extract is found to be beneficial in the treatment of diarrhea. Guajava leaf extract was examined for its efficacy in treating intestinal colonization caused by Citrobacter rodentium using a mouse model. The mouses were divided into two groups- control and test group, which were given normal saline and P. guajava leaf extract respectively. This was found that the mouse that were given 250µl of guava leaf extract for 3 consecutive days (twice a day) showed clearance of infection by the removal of bacteria through feces on the 4th day and showed complete removal of infection on 24th day, while the mouse in the control group continued to show infection till 29th day. Thus, we found that the guava leaf extract has the potential to treat bacterial diarrhea.